Judgment Based on Agreement of the Parties: Analysis from the Perspective of Practitioners’ Experience in Croatia - Elizabeta Ivičević Karas; Ante Novokmet; Igor Martinović (Utrecht Law Review, 2023)
The paper contains an analysis of judgments based on agreement of the parties, a Croatian model of plea bargaining, drawing on the experiences of three groups of practitioners: judges, state attorneys, and defence counsels. Previously conducted comparative legal analysis, as well as analysis of the Croatian normative framework and jurisprudence, was not able to provide answers to a number of questions about the motivation of the parties to negotiate, on the negotiation procedure which is not recorded in the protocol, about the real and the ideal role of the court, and about the real position of the parties and the victim. Hence, these issues were researched through semi-structured interviews with 60 practitioners and then further discussed in four focus groups. Some of the findings uncovered systemic inconsistencies in everyday legal practice in a number of areas. For instance, judgment based on agreement of the parties is more readily used in cases of serious offences, while other consensual forms of proceedings tend to be used for less serious offences. Informal negotiations at all stages of the criminal procedure have proven to be very popular with practitioners and sometimes even encouraged by judges. Yet, the issue of judicial control of the plea agreement divided the respondents, even though the right to judicial review of criminal prosecution is a fundamental principle of Croatian criminal procedure, which covers not only the fundamental issues of legality and voluntariness of the concluded agreement, but also the purposefulness of the proposed sanction. The victim’s position in the plea-bargaining procedure is considered to be adequate, at least as long as the victim is involved, and there is a tendency to consult the victim even in cases when his or her consent is not required by law. Finally, although it is generally considered that defence rights are well protected, there are problematic issues, namely tariffs or the ‘take it or leave it’ offer, as well as the wide discretion of the state attorney when deciding to enter into negotiations and reach agreement. The qualitative analysis of the findings, which is presented in this paper, should contribute to drafting specific proposals for improvements in the legislation and practice of the judgment based on agreement of the parties in Croatian law. Many of these findings may also be relevant for other legal systems, especially those of the continental European legal tradition, since they may face the same problems and questions related to plea bargaining as a global phenomenon.